IMPLEMENTASI KRIPTOGRAFI DENGAN ALGORITME ADVANCED ENCRYPTION STANDARD (AES-128) UNTUK PENGAMANAN FILE SOAL BERBASIS WEB PADA SMP GUNUNG JATI KOTA TANGERANG - Muhammad Arrafiqal Maryo; Bambang Wisnu Widagdo (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
Documents are one type of data file that is very important because it functions as a source of information needed by agencies or companies. In this ever-growing digital era, maintaining data confidentiality is very crucial for various agencies, one of which is the Education Agency. Gunung Jati Junior High School (JHS) in Tangerang City has implemented a computer-based examination system (USBK) since 2014. Although this system offers efficiency and convenience, the main problem faced is the weak security system for storing exam question files. This condition creates a significant risk, where important information can be stolen or manipulated, allowing for the leakage of exam questions which negatively impacts the integrity of the exam as well as student fairness. Therefore, in overcoming these problems the author plans to develop a cryptography-based web application by applying the AES-128 algorithm. This research aims to create a web-based application that can protect data by implementing the Advanced Encryption Standard (AES-128) algorithm method into the application to secure the file and provide a more interactive and in-depth learning experience for students through securing school exam data. The results showed that the application of AES-128 as an encryption method has proven effective in increasing the security of question files at Gunung Jati Junior High School and making it the right choice to protect sensitive data. Keywords: Advanced encryption standard (AES-128), data security, encryption, file security, information security.